Presentation and management of nasal foreign bodies in a Chinese metro area. Issue 16 (23rd April 2021) - Yan, Shang; Zeng, Nan; Chen, Guowei; Chen, Yongchao; Wu, Zebin; Pan, Hongguang; Teng, Yishu; Ma, Xiangyu; Li, Lan
Abstract : Abstract: Nasal foreign bodies in children are common complaints encountered by pediatric otolaryngologists. We investigated clinical features, diagnosis, and treatment of nasal foreign bodies in children in a Chinese metro area. Six hundred sixty eight children with nasal foreign bodies presented to Shenzhen Children's Hospital, diagnosed and treated by the authors were enrolled from January 2016 to October 2019, causes for medical consultation, age, sex, duration, types, locations, removal, and complications were recorded and analyzed. Nasal foreign bodies were common in children between 1 and 5 years of ages (96.8%). The right nasal cavity (61.4%) was the most common site for foreign body insertion (61.4%). Most of the children (89.4%) presented for a complaint of nasal discomfort or foreign body insertion themselves, or for foreign body impaction discovered by the caregivers. Most of the foreign bodies (85.0%) were discovered within 1 day. The most nasal foreign bodies were the whole toys and toy parts (34.1%). The majority of nasal foreign bodies (99.1%) located in the antero-inferior portion of the nasal cavities and could be removed with simple instruments. The occurrence of complications in nasal foreign bodies (10.2%) was not common. The present study objectively exhibited clinical features, diagnosis, and treatment of nasal foreign bodies in a Chinese metro area.